2011
DOI: 10.1002/hbm.21470
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural activation in ornithine transcarbamylase deficiency during executive cognition: An fMRI study

Abstract: Background Ornithine transcarbamylase deficiency (OTCD) is an X-linked urea cycle disorder characterized by hyperammonemia resulting in white matter injury and impairments in working memory and executive cognition. Objective To test for differences in BOLD signal activation between subjects with OTCD and healthy controls during a working memory task. Design, Setting and Patients Nineteen subjects with OTCD and 21 healthy controls participated in a case-control, IRB-approved study at Georgetown University M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
5
26
0
Order By: Relevance
“…We hypothesize that asymptomatic participants only demonstrate cognitive deficits in executive function and motor tasks when challenged. This has also been observed in fMRI studies evoking working memory task of increasing difficulty 19 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We hypothesize that asymptomatic participants only demonstrate cognitive deficits in executive function and motor tasks when challenged. This has also been observed in fMRI studies evoking working memory task of increasing difficulty 19 .…”
Section: Discussionsupporting
confidence: 66%
“…Recently, more targeted studies have evaluated the extent of the neurological damage caused by hyperammonemic episodes and the regions of the brain that are most sensitive to these effects 19 . Our recent imaging study found that white matter in the frontal lobe is predominantly affected during hyperammonemic episodes in OTCD patients 21 , adding to our understanding of executive dysfunction in OTCD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on OTCD populations found increased activation in frontal regions, including the ACC, relative to controls despite a lack of differences in task performance, suggesting a model of prefrontal inefficiency [49]. It is possible that this increased ACC activity is a mechanism employed to compensate for the poor connectivity between the ACC and other areas critical for executive functioning, such as the insula, IPL, and SFG, as demonstrated by the current study.…”
Section: Discussionsupporting
confidence: 59%
“…In a task-related fMRI design, a subject is placed in the magnet and scanned while performing various types of cognitive or motor tasks. We used two working memory tasks, the color STROOP and N-back which we have previously described [30]. …”
Section: Imaging Toolsmentioning
confidence: 99%
“…In addition, we observed accessory activation of regions not seen in controls. The effects of cognitive inefficiency intensified in the 2 back conditions of the testing [30]. …”
Section: Lessons Learned From Seven Years Of Imaging Otcd and Relamentioning
confidence: 99%